2007
DOI: 10.1080/08920750601169642
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Behavior in a Boating Speed Zone

Abstract: The greatest source of human-related mortality for endangered Florida manatees is collisions with watercraft. Regulation of boat speeds is the principal management tool to minimize this threat. Demands on law enforcement limit their ability to monitor boater behavior and managers seek alternative strategies to increase compliance. The purposes of this study were to: (1) explore the effectiveness of an on-site sign to enhance boater compliance in a boating speed zone, and (2) Conservation Commission, unpublish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Robson Bight (Michael Bigg) Ecological Reserve (Jelinski, Kryeger, & Duffus, 2002); Stewallegn Bank National Marine Sanctuary (Wiley, Moller, Pace, & Carlson, 2008); The Indian River North/Packwood Place manatee slow-speed sanctuary (Sorice, Flamm, & McDonald, 2007)). Underpinning the TBSZ designation is an advanced legislative framework (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Robson Bight (Michael Bigg) Ecological Reserve (Jelinski, Kryeger, & Duffus, 2002); Stewallegn Bank National Marine Sanctuary (Wiley, Moller, Pace, & Carlson, 2008); The Indian River North/Packwood Place manatee slow-speed sanctuary (Sorice, Flamm, & McDonald, 2007)). Underpinning the TBSZ designation is an advanced legislative framework (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Self-regulation and education do not seem to have successfully protected cetaceans in Port Phillip Bay, Victoria [108,110]. Some international studies have concluded that education and outreach, named 'passive actions', are ineffective for improving vessel compliance with regulations [111,112], while the first listed item, the presence of police enforcement, proves effective [108,113]. Constantine [114] names the Western Australian government's decision to withdraw two dolphin-watching permits in Shark Bay as the most effective management strategy, a decision which came after a significant impact from the dolphin watching tours was shown.…”
Section: Management Recommendationsmentioning
confidence: 99%
“…Although specific speed limits were not forwarded by respondents, literature about areas with similar concerns, such as parts of Florida, suggests implementing idle/slow or no-wake speed limits in order to significantly reduce negative impacts associated with high boat speeds (Nanson, et al, 1994;Sorice, et al, 2007). These literatures also highlight the importance of regular enforcement in order to ensure boater compliance.…”
Section: Suggestions For Improved Boat Traffic Managementmentioning
confidence: 99%
“…Such signs are commonly used in creating and posting speed zones (e.g. Gorzelany, 2004;Sorice, Flamm, & McDonald, 2007),…”
Section: Speed Limits Emerge As the Main Suggestionmentioning
confidence: 99%